2018
DOI: 10.1080/10410236.2018.1437527
|View full text |Cite
|
Sign up to set email alerts
|

Picture Yourself Healthy—How Users Select Mediated Images to Shape Health Intentions and Behaviors

Abstract: Hypotheses on how selective viewing of mediated images may sustain eating habits and aid healthier eating were derived from the Selective Exposure Self- and Affect Management model. The model posits that individuals select to view media to manage their self-concepts-and that this exposure affects subsequent intentions and behaviors. Participants (N = 265) selectively viewed Instagram-like postings featuring healthy or unhealthy food imagery. Beforehand, participants reported habits and perceived expert recomme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 24 publications
2
7
0
Order By: Relevance
“…Our study revealed the positive correlation between appearance comparison and sexual initiation assertiveness. The results may occur because appearance comparison is associated with self-improvement: an interest in advancing oneself to decrease the discrepancy between oneself and their ideal(s) (Westerwick et al, 2017; Wilson et al, 2019). Research (Westerwick et al, 2017) suggested that perceived discrepancy between oneself and an ideal behavior is positively related to the person’s attention to information that might help them obtain the ideal.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Our study revealed the positive correlation between appearance comparison and sexual initiation assertiveness. The results may occur because appearance comparison is associated with self-improvement: an interest in advancing oneself to decrease the discrepancy between oneself and their ideal(s) (Westerwick et al, 2017; Wilson et al, 2019). Research (Westerwick et al, 2017) suggested that perceived discrepancy between oneself and an ideal behavior is positively related to the person’s attention to information that might help them obtain the ideal.…”
Section: Discussionmentioning
confidence: 99%
“…Research (Westerwick et al, 2017) suggested that perceived discrepancy between oneself and an ideal behavior is positively related to the person’s attention to information that might help them obtain the ideal. However, Wilson and colleagues (2019) argued that the perceived discrepancy and one’s biases towards information or attitudes associated with the ideal achievement could be negatively correlated. Mixed results across the studies (Westerwick et al, 2017; Wilson et al, 2019) are perhaps because of the use of different experimental stimuli.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations